2022
DOI: 10.1371/journal.pone.0279212
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic health expenditure on chronic non-communicable diseases among elder population: A cross-sectional study from a sub-metropolitan city of Eastern Nepal

Abstract: Introduction This study was conducted with the objective to analyze the out-of-pocket (OOP) healthcare expenditure and catastrophic healthcare expenditure (CHE) on chronic non-communicable diseases (CNCD) among the elderly population, and the association of CHE on CNCD with associated factors among the same population. Materials and methods We collected data from the elderly population of Dharan Sub-metropolitan city of the Eastern Nepal via door-to-door survey and face-to-face interview. The ten wards out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This might be due to the fact that single individuals do not have either spouse or family members to support financially for healthcare, or because single people tend to be physically and mentally less healthy due to less social support from the spouse and family, thus increasing their expenditures for health. This result is in line with studies which showed single unmarried respondents have higher CHE (25,(32)(33)(34) and different from studies which showed married households were more likely to incur CHE (35)(36)(37).…”
Section: Discussionsupporting
confidence: 81%
“…This might be due to the fact that single individuals do not have either spouse or family members to support financially for healthcare, or because single people tend to be physically and mentally less healthy due to less social support from the spouse and family, thus increasing their expenditures for health. This result is in line with studies which showed single unmarried respondents have higher CHE (25,(32)(33)(34) and different from studies which showed married households were more likely to incur CHE (35)(36)(37).…”
Section: Discussionsupporting
confidence: 81%
“…The conducted study by Brinda et al 18 reveals that 7% of the older people in India are encountered with CHE. Also, the CHE prevalence in older people with chronic noncommunicable in Nepal is 14.6% 19 …”
Section: Discussionmentioning
confidence: 99%
“…High out-of-pocket payments are associated with catastrophic and impoverished spending and can potentially lead to financial hardship, especially among the poor [ 8 ]. Some low-income countries have poor financial health systems in healthcare or do not provide adequate financial protection, resulting in a high risk of catastrophic health expenditures [ 9 , 10 ]. The Malaysian national healthcare system provides financial risk protection through universal access to a comprehensive package of government-guaranteed healthcare services and charging low user fees in the public health system [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%